2014
DOI: 10.1080/07448481.2013.877018
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Measured Versus Self-reported Physical Activity in College Students: Implications for Research and Practice

Abstract: Estimation of college students' level of PA may require interpretation of data from different measurement methods, as self-report and accelerometry generate different estimations of PA in college students who may be even less active than previously believed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 29 publications
3
50
5
2
Order By: Relevance
“…The participants in this research averaged a high amount (1.1 hr) of MVPA every day. This is similar to findings by Raynor and Jankowiak () though three times as much as Downs et al (). Neither of these groups explored SB.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The participants in this research averaged a high amount (1.1 hr) of MVPA every day. This is similar to findings by Raynor and Jankowiak () though three times as much as Downs et al (). Neither of these groups explored SB.…”
Section: Discussionsupporting
confidence: 92%
“…Three sources helped guide estimation of the appropriate sample size for the study: 1) previous similar research; 2) general statistical principles; and 3) the nQuery (Statistical Solutions, Ltd., Los Angeles, CA) power analysis program. Sample sizes in similar research ranged from 77 (Downs, Van Hoomissen, Lafrenz, & Julka, ) to 168 (Raynor & Jankowiak, ). General consensus on principles of statistics suggest multiple regression analyses should have 10–15 participants per independent variable (Harrell, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies relied on subjective self-report measures to assess physical activity (e.g., Peeters et al, 2015), which have been shown to be less reliable than objective measurement (Downs, Van Hoomissen, Lafrenz, & Julka, 2014). In addition, most previous studies were cross-sectional, and as a result, could not examine the temporal order of self-efficacy and physical activity.…”
Section: Self-efficacy and Physical Activity In People With Oamentioning
confidence: 99%
“…Estimating the appropriate sample size was based on number of participants used in similar research 55,56 and following general consensus on principles of statistics which indicate multiple regression analyses should have [10][11][12][13][14][15] participants per independent variable. 57 Estimates using the program nQuery recommended a minimum of 59-65 subjects to achieve 80% power to determine meaningful associations between our factors of interest.…”
Section: Power Analysismentioning
confidence: 99%